Pertumbuhan Musik Klasik Barat di Kota Medan - Elfrida Yuliana Simamora (Lembaga Pengembangan Kinerja Dosen, 2024)
Edward Van Ness is a violinist, conductor, writer and teacher who has lived and worked in Indonesia cumulatively for more than forty years. Composition and world music studies were completed at Wesleyan University, conducted at the Eastman School of Music, with further graduate studies also at Boston University. He undertook research on South Indian Classical Music, was a concert player in the Carnatic Vina, and founded the Madras Chamber Orchestra. He founded the music department in 1986 at the Medan International School and became head of the music and technology department at the Indonesian Music Academy, University of North Sumatra and HKBP Nommensen University. A founder of the Indonesian Promusik group. Also known as the conductor and artistic director of the first complete performance of Handel's historic Messiah with the Ensemble Nommensen and Promusika in 1987 (in the original Baroque performance style). He is also known as the first musician invited by the institution and the Vietnamese government by leading the orchestra with cellist Cecylia Barczyk from the Ho Chi Min Conservatory Orchestra in Vietnam in April 2005. Since 2003 he has led the Nusantara Symphony Orchestra in many concerts. . Most recently he was the music director and conductor of the Indonesian National Christmas celebration in December 2018 in Medan. Until now he is a Music Teacher at the Sumatra Conservatoire.